Síntesis y caracterización de vanadio a partir de anodización electroquímica (2024)
The present research focuses on the anodization of vanadium sheets, a material that has been a source of studies due to its characterization and oxidation states thanks to its application possibilities and synthesis capacity. Molybdenum will be used as a dopant (a material that has cytotoxicity and a structure similar to vanadium) to analyze the alterations that the ionic currents would suffer through the anodic oxide on the vanadium and the electrostatic field produced. Finally, the sheets will be characterized using RAMAN, X-ray diffraction and scanning electron microscopy in order to identify their structural, optical and morphological properties. Among the most notable results is the predominant presence of vanadium dioxide, although some areas suggest the presence of vanadium (V) oxide, possibly due to the fragmentation of the orthorhombic structure of the pentoxide, leading to a new structure. The samples also featured the appearance of nanowires, which makes it possible to enhance the conductivity capabilities in electronic circuits to promote it as a smart material.